2022
DOI: 10.1126/sciadv.abq6974
|View full text |Cite
|
Sign up to set email alerts
|

Ocean currents break up a tabular iceberg

Abstract: In December 2020, giant tabular iceberg A68a (surface area 3900 km 2 ) broke up in open ocean much deeper than its keel, indicating that the breakage was not immediately caused by collision with the seafloor. Giant icebergs with lengths exceeding 18.5 km account for most of the calved ice mass from the Antarctic Ice Sheet. Upon calving, they drift away and transport freshwater into the Southern Ocean, modifying ocean circulation, disrupting sea ice and the marine biosphere, and potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…For strong discharge events it might be useful to prevent icebergs from covering more than 100% of the grid area. The iceberg module could also be advanced by improving the physics, for example, by accounting for huge icebergs and their breakup (England et al., 2020; Huth, Adcroft, & Sergienko, 2022; Huth, Adcroft, Sergienko, & Khan, 2022; Stern et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For strong discharge events it might be useful to prevent icebergs from covering more than 100% of the grid area. The iceberg module could also be advanced by improving the physics, for example, by accounting for huge icebergs and their breakup (England et al., 2020; Huth, Adcroft, & Sergienko, 2022; Huth, Adcroft, Sergienko, & Khan, 2022; Stern et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To uphold the plane strain assumptions of our fracture theories when comparing with observations, we develop a strain rate criteria in Supporting Information S1 to validate locations where the flow is approximately 1D and Mode I fracture is applicable. In reality, ice shelves can also have their stress states altered due to 3D effects such as shear fractures (van der Veen, 1999) and torque from ocean currents (Gomez-Fell et al, 2022;Huth et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In Antarctica, basal crevasses may initiate rifts that can propagate across the ice shelf and calve icebergs (Lipovsky, 2020). These icebergs can transport fresh melt-water equatorwards and threaten biodiversity of islands in the Southern Ocean (Huth et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While some modeling studies ignore sea ice forcing of icebergs (e.g., Andersson et al., 2016; England et al., 2020; Kubat et al., 2005; Parayil et al., 2022; S. D. Smith, 1993; Turnbull et al., 2015; Wagner et al., 2017), especially if they are focusing on generally ice‐free areas, most models (e.g., Bigg et al., 1997; Gladstone et al., 2001; Huth, Adcroft, Sergienko, & Khan, 2022; Jongma et al., 2009; Kulakov & Demchev, 2015; Marsh et al., 2015; Martin & Adcroft, 2010; Merino et al., 2016; Stern et al., 2016) assume that the sea ice force Fsi ${\vec{F}}_{si}$ can be parameterized as a drag force (refer to Equation ). However, a study conducted by Lichey and Hellmer (2001) that compared modeled and observed trajectories for a tabular iceberg in the Southern Ocean, found that the parameterized sea ice drag force was not enough to reproduce observations at high sea ice concentrations.…”
Section: Introductionmentioning
confidence: 99%